Políticas públicas de inovação e o desenvolvimento: o caso do setor moveleiro de Campina Grande - PB - Oliveira, Ana Carla Souto de (2018)
The objective of this dissertation is discussing the relations between public policies of innovation and development, based on the case study of the furniture sector of Campina Grande / PB. The theoretical perspective includes the debate about innovation, its relation with development, traversing the classical literature and the latest on the theme, more specifically that which interfaces innovation and development. The methodology included the analysis of national public policies in the area of Innovation and for the case study, the collection of secondary data produced by FIEP-PB on the furniture sector of Campina Grande / PB. Structured interviews were carried out with an intentional sample of producers of furniture in the municipality, regarding their ways of conceiving and appropriating public policies related to the promotion of innovation. Among the main conclusions of the present study, we highlight the following: (1) the furniture production sector of the city of Campina Grande / PB is relevant to the local economy in terms of productivity and employment and income generation; (2) the predominant profile of local furniture producers is micro-small entrepreneurs, predominantly among them incremental innovation, improvement of machinery, manual labor processes, based on imitation of existing products in the market and based on feedback from customers; and (3) Most CG / PB furniture producers interviewed do not access the government's public innovation policies, which they see as large producers.